In vitro regeneration and evaluation of phytochemical and antimicrobial activity of kunyit putih [Curcuma zedoaria (Christm.) Roscoe] - Alghannay, Khalid Abubaker (2019)
Today’s healthcare system is hampered with numerous health problems such as degenerative disorder, chronic diseases, resistant infection etc. Plants are source of precursors of many natural products and secondary metabolites with pharmacological and therapeutic potentials but some major set-back in plant natural product medicines are non-availability of medicinal plant material and in-ability to extract the bioactive compounds with the appropriate solvent. Therefore, there is highly need to develop an in vitro micro propagation technique for rapid multiplication to produce high quality planting materials of C. zedoaria, which is suffering from persistent endophytic and epiphytic microbial contamination and from low response to media, and to evaluate the phytochemicals screening method to explore their antioxidant compounds and antimicrobial properties. Some procedures do exist but generally do not address well the initial stage of culture establishment and phytochemical screening as well. Hence, the objectives of this study is to establish an in vitro regeneration protocol for C.zedoaria using tissue culture techniques. Secondly to optimize ideal solvent and concentrations suitable for screening the phytochemicals of C. zedoaria leaves and rhizome for Total Phenolic Content (TPC), Total Flavonoids Content (TFC) and Antioxidant activity (AO). The most suitable solvents (isopropanol for TPC and AOC/ methanol for TFC), from last experiment results, were applied as the third objective, as comparative study, to examine the extent of the difference between (NFGP) and (TCPP). Eventually, the evaluation of the antimicrobial activity of the different solvents and oils extracted from the leaves and rhizomes of C. zedoaria against pathogenic bacteria was carried out. Surface sterilization were assessed on explants (rhizome with apical buds), with 3 different sterilizing agents (NaOCl, HgCl2 and Nano Silver) at different concentrations and immersion times, in attempt to determining the most suitable method of reducing explant contamination. We detect the ability of 6-benzylaminopurine (BAP) alone for shoot induction, while (BAP), kinetin, and thidizuron (TDZ) were individually evaluated for shoot formation, however IBA and NAA was used separately to stimulate root formation. To screen for phytochemicals constituents, the leaf and rhizome of C. zedoaria were extracted with different polar solvents including ethanol, methanol, dimethyl sulfoxide, acetonitrile, acetone, isopropanol, and glycerol with different concentrations (0.0, 10, 30, 50, 70, 90, and 100%), We used Folin Ciocalteu’s reagent, DPPH scavenging assay and colorimetric method using Alumunium Chloride, to determined TPC, AOX and TFC successively, while Disk Diffusion Test and also Minimum and Bactericidal Inhibitory Concentration (MIC and MBC) tests, was used to evaluate the antimicrobial activities. The results revealed that NaOCl was the most suitable sterilizing agent with 77.77% of sterilized success and survived explants compared to HgCl2 and NS after decontamination stage. The shoot induction and formation results showed that 3 mg/L of BAP strongly stimulated the shoot formation of C. zedoaria by producing 4.3 shoots per explants when compared to kinetin and TDZ. In evaluating the effects of different auxins on root induction of C. zedoaria revealed that 2.0 mg/L of NAA produced the highest root number by the mean of 6.3 roots per explant in C. zedoaria compared to other auxin hormonal treatments. The shoot induction and formation results showed that 3 mg/L of BAP strongly stimulated the shoot formation of C. zedoaria by producing 4.3 shoots per explants when compared to kinetin and TDZ. In evaluating the effects of different auxins on root induction of C. zedoaria revealed that 2.0 mg/L of NAA produced the highest root number by the mean of 6.3 roots per explant in C. zedoaria compared to other auxin hormonal treatments. The result of the phytochemical assay revealed that the highest flavonoid content in leaf tissue (3.309 mg) was achieved using dimethyl sulfoxide solvent (70%), methanol at 90% (3.01 mg), followed by 90% ethanol with a value of 2.7 mg, while in the rhizome, methanol displayed the highest concentration at 100 and 90 % by 4.8 and 4.5 mg respectively. Our finding showed that the Isopropyl alcohol was promising option for evaluating (AOC) and (TPC) due to its extractability potential on both Leaves & Rhizome tissues, while the Methanol is most suitable solvent for (TFC) in both cases too, despite competition and convergence of solvent impact. However, there was no significant difference in leaf and rhizome content for phytochemicals measured (TFC, TPC and AOC) in both NFGP and TCPP, hence there were no real differences using this propagation method (tissue culture) in certain phytochemical content. The antimicrobial inhibitory effect of C. zedoaria against certain pathogenic gram positive and gram negative revealed that these positive effects were present at all levels of all extracts (solvents, concentrations and type of tissues) and same is true for the effect of oil samples. This effect is incremental by increasing concentration each time. The effect of rhizome extract is relatively higher than that of leaf extract at all concentrations whereas, the solvent type did not have any obvious effect on inhibition, although minor effect was observed with isopropanol. The most MIC & MBC results is within the range of medium-impact rates, which has positive connotations and distinguished implications. In conclusion, C. zedoaria can be effective to treat diseases caused by bacterial infections.